Researches regarding the static and dynamic behaviour of composites with natural reinforcements. Issue 1 (December 2020) - Rădoi, A I; Miriţoiu, C M; Bogdan, M; Stănescu, M M; Bolcu, D
Abstract: In this paper, some composite materials were built in this way: the reinforcement is made with natural fibers (there were used two types of natural fibers in this way: hemp and cotton) and the matrix is made from epoxy resin. The Resoltech 1050 epoxy resin is used, with its Resoltech 1050 hardener. The casting was made at room temperature and the matrix was applied using the brush. The static experimental conditions are characterized by tensile loading of the build specimens and the determination of statically Young modulus. There was used an Instron Universal testing machine and the force-extension curves were obtained. The dynamic parameters were determined from the bars free vibrations. The next experimental montage was used: the bars were clamped at one end and were left free at the other end. At the free end, a Bruel&Kjaer accelerometer with 0.04 pC/ms −2 sensitivity was placed in order to record the beams dynamic response. A force was applied at the free end to bend the beams and after bending, the force was cancelled and the beams were left to freely vibrate. The accelerometer was connected to a signal conditioner Nexus and the signal conditioner was connected to a data acquisition system SPIDER 8 made by Hottinger Baldwin Messtec. The acquisition system was connected to a notebook and the experimental parameters were obtained through CATMAN EASY software. From the free vibrations recording, the next mechanical parameters were determined: the eigenfrequency of the first eigenmode, the damping factors per unit mass and per unit length, the loss factor and the dynamic Young modulus.